2015
DOI: 10.3758/s13415-015-0376-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of stimulus complexity on the preattentive processing of self-generated and nonself voices: An ERP study

Abstract: The ability to differentiate one's own voice from the voice of somebody else plays a critical role in successful verbal self-monitoring processes and in communication. However, most of the existing studies have only focused on the sensory correlates of self-generated voice processing, whereas the effects of attentional demands and stimulus complexity on self-generated voice processing remain largely unknown. In this study, we investigated the effects of stimulus complexity on the preattentive processing of sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 129 publications
(206 reference statements)
4
7
0
Order By: Relevance
“…For example, when judging the self-referential content of positive and negative words, participants were faster in judging positive words uttered by themselves than by an unknown speaker (Watson et al, 2007). Moreover, word discrimination was easier than vocalisation discrimination and agrees with prior studies that showed that the processing of speech (with verbal content) compared to vocalisations (no verbal content) is subserved by different neurocognitive mechanisms (Belin et al, 2004;Conde et al, 2015;Pell et al, 2015). Contrary to our hypothesis and prior evidence (Chhabra et al, 2014), we observed that discrimination was affected by HP.…”
Section: The Role Of Hallucination Predisposition In Self-other Voicesupporting
confidence: 84%
See 2 more Smart Citations
“…For example, when judging the self-referential content of positive and negative words, participants were faster in judging positive words uttered by themselves than by an unknown speaker (Watson et al, 2007). Moreover, word discrimination was easier than vocalisation discrimination and agrees with prior studies that showed that the processing of speech (with verbal content) compared to vocalisations (no verbal content) is subserved by different neurocognitive mechanisms (Belin et al, 2004;Conde et al, 2015;Pell et al, 2015). Contrary to our hypothesis and prior evidence (Chhabra et al, 2014), we observed that discrimination was affected by HP.…”
Section: The Role Of Hallucination Predisposition In Self-other Voicesupporting
confidence: 84%
“…Overall, discrimination was affected by stimulus type, voice identity, and the emotional quality (valence) of the voice: judgments of acoustic similarity were improved when participants listened to words rather than vocalisations and specifically when positive content words were uttered by the participant. The results of the discrimination task (involving a simple differentiation of self and other voices) agree with a noted processing advantage associated with self-generated voices (e.g., Conde et al, 2015). One's own voice represents a more familiar signal, which is more easily matched with speaker-specific stored representations (Belin et al, 2011;Blank, 2002;Nakamura et al, 2001).…”
Section: The Role Of Hallucination Predisposition In Self-other Voicesupporting
confidence: 75%
See 1 more Smart Citation
“…These results confirmed a previous report of a distinct process between self and familiar voices [4]. On the other hand, given that externally generated familiar voices are never heard as self-generated voices, it is difficult to extrapolate results on self voices to processes of voice recognition and identification [and see [57][58][59][60]. On their side, Holeckova, Fischer [61], after exposing participants to their own name pronounced by intimately familiar and unfamiliar speakers, reported a small effect on the P3, between 300 and 380 ms, but mostly on later-occuring ERP between 625 and 800.…”
Section: On the Neural Underpinnings Of Voice Discrimination Recognisupporting
confidence: 86%
“…For example, the amplitude of the P3a component in a passive oddball paradigm was observed to be lower for self-voice, compared to unfamiliar (Graux et al 2013) and familiar voices (Graux et al 2015), suggesting less pre-attentional processes being involved in the discrimination of one's own voice. (Conde et al 2016) confirmed this finding and narrowed the P3 reduction down to experimental stimuli consisting of simple vocalizations, compared to words. However, in active oddball paradigms requiring attentional processes, the P3 amplitude increased for self-voices compared to other voices, indicating that one's own voice has a greater affective salience than an unfamiliar voice (Conde et al 2015(Conde et al , 2018.…”
Section: Introductionmentioning
confidence: 54%